MOBILE AUDIOBOOKS, LISTENING COMPREHENSION AND EFL COLLEGE STUDENTS - Al-Jarf, Reima (International Journal of Research -GRANTHAALAYAH, 2021)
This article proposes the integration of mobile () to develop EFL college students' listening comprehension skills. It aims to show the following: (i) The advantages of integrating in listening instruction; (ii) sources of ; (iii) how to search for ; (iv) criteria for selecting ; (v) examples of ; (vi) listening comprehension skills and literary appreciation skills that can be developed through supplementary ; (vii) phases of teaching and learning with and types of tasks that can be used with MAB; (viii) evaluation and assessment; (ix) the effect of on listening comprehension skill improvement and attitudes as perceived by the students; and (x) recommendations for the effective use of .